2015
DOI: 10.1186/s13104-015-1553-6
|View full text |Cite
|
Sign up to set email alerts
|

Health workers’ knowledge on future vascular disease risk in women with pre-eclampsia in south western Nigeria

Abstract: Background Pre-eclampsia progressing to eclampsia is one of the major causes of maternal death in Nigeria. Since there is long term association of pre-eclampsia with cardiovascular disease, cerebrovascular disease, renal disease, short life expectancy and mortality, it is essential to obtain obstetric history for better counseling and long term monitoring. The study assessed the knowledge of health workers about the association of pre-eclampsia with future cardiovascular disease and offering any risk-reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
(22 reference statements)
2
14
0
Order By: Relevance
“…Only one study has examined knowledge of HCPs on long-term health risks after both PE and GH, whilst all others focus on risks after PE only [ 15 ]. In line with another study that found that higher knowledge was associated with belonging to a particular profession [ 16 ], we found higher knowledge among medical professionals compared with midwives. However, in contrast to an American study that found obstetricians generally had more awareness of CVD after PE than internal medicine physicians [ 17 ], cardiologists were the highest scoring profession in this survey, DRANZCOG GPs and obstetricians were quite similar.…”
Section: Discussionsupporting
confidence: 92%
“…Only one study has examined knowledge of HCPs on long-term health risks after both PE and GH, whilst all others focus on risks after PE only [ 15 ]. In line with another study that found that higher knowledge was associated with belonging to a particular profession [ 16 ], we found higher knowledge among medical professionals compared with midwives. However, in contrast to an American study that found obstetricians generally had more awareness of CVD after PE than internal medicine physicians [ 17 ], cardiologists were the highest scoring profession in this survey, DRANZCOG GPs and obstetricians were quite similar.…”
Section: Discussionsupporting
confidence: 92%
“…Out of the 12 studies, six addressed women's knowledge (11, 1316, 23), five addressed HCP's knowledge (2428) and one addressed both women and HCP (12). The studies include eight quantitative (surveys, chart reviews) (15, 16, 2328) and four qualitative studies (1114) (focus group, group interview, semi-structured interviews).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were conducted in the United States of America (USA) (1315, 27, 28) two from Canada (12, 26) one each from Australia (23), Germany (25), Nigeria (24), Portugal (16), and the United Kingdom (UK) (29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7] It is an urgent problem and one of the main causes of hospitalization in maternity hospitals, being a precursor of complications during pregnancy, childbirth and puerperium and even several years after childbirth. 8 It is also linked to neonatal complications such as prematurity, intrauterine growth restriction (CIUR), low birth weight and fetal death. 9 It is exposed that, thus associated with Vogt-Koyanagi-Harada syndrome, SHEG potentiates effects for the individual, which makes the accompaniment of autoimmune disease and hypertensive syndrome complex, concomitantly representing a higher maternal-fetal risk with high morbidity and psychological attrition and physiological exacerbation.…”
Section: Original Articlementioning
confidence: 99%